Evaluation of the thermal effusivity of intermetallic compounds using a modulated thermoreflectance method. (1st June 2022) - Nakamura, Fumiya; Murakami, Taichi; Miyake, Shugo
Abstract: In this study, we evaluated thermal properties of the matrix phase and intermetallic compounds in solder joints by a frequency-domain thermoreflectance method with high spatial resolution realized by two two laser beams and considering thermal diffusion length. The values of the thermal effusivities of a tin matrix phase (Sn matrix) and the intermetallic compounds (IMCs) in solder joints were determined for each heating frequency using calibration curves given by standard samples with known thermal properties. These measured heat effusivities of these Sn matrix and IMCs were estimated various values affected thermal conductivity of addition elements. Moreover, to convert from thermal effusivity to thermal conductivity, numerical calculations were conducted with assumed various thermal conductivity of molybdenum-reflector film on the sample surface and the volumetric heat capacity of IMCs. Finally, it is found that the apparent thermal conductivity of the Mo film was 0.5 W m −1 K −1 and the thermal conductivity of IMCs were shown 25–37 W m −1 K −1 with composition dependence clearly.